Book review: Bhaswati Mukherjee, India and EU: An Insider's View. (December 2019) - Sachdeva, Gulshan
Bhaswati Mukherjee, India and EU: An Insider's View . New Delhi: ICWA and Vij Books, 2018, pp. +336, ₹995.